The Effect of dietary induced hypercholesterolemia on the lipid profile and some enzyme activities in Wistar male rats. - El-gamal, El-Khedr Mohamed Mostafa (Journal of medical and pharmaceutical sciences, 2017)
Aim of study: To investigate the effects of high dietary soybean oil and cholesterol on the serum lipid profile, enzymes and biochemical changes in weanling Wistar rat’s male. Materials and Methods: Twenty weanling male Wistar rats organised equaliy into two groups were used in this study. The first group of rats, were fed with controlled diet made up of the normal rat chow (C), and the second group was fed with hypercholesterolemia diet (HPC) enriched with 25% soybean oil and 1% cholesterol for eight weeks. Results: The dietary intake of the HPC diet was significantly increased the level of total cholesterol (TC), LDL-C and triglycerides (TG) in the serum of Wister rats fed with HPC diet. gamma glutamyl transferase (GGT), aspartate amino transferase (AST) and alanine amino transferase (ALT), activities were also markedly elevated in rats fed with HPC diet; while, total protein and glucose level of rats fed with HPC diet was remarkably reduced, no significant difference was found in the high density lipoprotein cholesterol (HDL-C) and albumin contents of both groups. Conclusion: This study established that hypercholesterolemia is induced by high soybean oil/cholesterol diet, despite the fact that soybean oil has high content of polyunsaturated fatty acids. In addition, the HPC diet led to weight loss in the rats and caused injury of rats’ heart and liver.